Decoding the epigenetic-immune nexus in hepatocellular carcinoma: a Mendelian randomization study reveals BTN3A2, S100A12 and TRIM27 as white blood cell regulators - Yang Qiu; Haiyan Zhang; Xiao Yu; Jielu Pan; Dinghong Xiao; Hongyu Miao; Ruiqing Wang; Nan Shen; Peimin Pu; Yinling Zhou; Zhidong Liu; Lin He; et al. (BMC Cancer)
Abstract Background Hepatocellular carcinoma accounts for 90% of primary liver malignancies and ranks as the fourth leading cause of global cancer mortality. DNA methylation drives HCC pathogenesis by orchestrating tumor suppressor silencing and oncogenic pathway activation, fundamentally governing tumor heterogeneity and therapeutic resistance. While alterations in white blood cell counts have emerged as independent prognostic indicators in HCC progression, their causal relationship with tumor epigenetics remains unclear. Given that HCC tumors actively secrete cytokines and remodel systemic immunity through epigenetic mechanisms, peripheral white blood cell dynamics serve as a compelling surrogate for studying tumor-driven immune dysregulation and identifying methylation-based therapeutic targets. Methods We integrated DNA methylation profiles from The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) with summary statistics from six genome-wide association studies of white blood cell counts. Using these data, we applied a two-sample Mendelian Randomization (MR) framework to systematically investigate the causal effects of HCC-related CpG sites on white blood cell counts. The robustness of our findings was established through stringent criteria, comprehensive sensitivity analyses, and Bayesian colocalization, followed by functional validation with TCGA data and a transcriptome-wide association study (TWAS). Results Our analysis identified 26 HCC-specific CpG sites with causal effects on white blood cell counts. A multi-step validation pipeline integrating Bayesian colocalization and tumor-specific expression analysis robustly confirmed three core mediator genes: BTN3A2, TRIM27, and S100A12. TWAS provided independent, gene-level validation, revealing BTN3A2 as a powerful regulator of lymphocyte and neutrophil counts, TRIM27 as a key immunometabolic checkpoint, and S100A12 as a modulator of innate immunity. Conclusion This study establishes epigenome-immune crosstalk in HCC by identifying BTN3A2, S100A12 and TRIM27 as central methylation-immunoregulatory hubs. The discovered methylation-immune axes provide mechanistic insights for developing combination therapies targeting epigenetic checkpoints to reverse immunosuppressive microenvironments in advanced HCC.